SOME CONSIDERATIONS REGARDING CCR DEC. NO. 364/2022 - Marta-Claudia CLIZA (Challenges of the Knowledge Society)
The issue of plagiarism has raised many theoretical and practical discussions. Also, the legal basis was not clear enough and certain misunderstandings have created the premises for losing the title of doctor. Arrived in court, the trials were judged differently. In 2022, CCR pronounced dec. no. 364, one of the clearest decisions of the court, and the issue was settled in a transparent manner. The current study will analyse the implications of this decision.